The income of nation : part one: history (with corrections and emendations) - Studenski, Paul (New York : New York University Press, 1961)
This book emphasized the historical background of the existing national income concepts, estimates and critical appraisal than the earlier version.
Bibliography pp.163-177
osa; 21/09/18
Loans
Keywords: Income; National income